The effects of channa striatus compared with glucosamine sulphate in serum cartilage and inflammatory markers in knee osteoarthritis patients - Koon, Tan Say (2019)
Knee osteoarthritis (KOA) is one of the commonest types of osteoarthritis (OA). Currently, the treatment is to provide the pain relief to OA patients. The concern for the side effects of current treatment encouraged the studies to search for natural products to reduce the side effects. Channa striatus (CS) is a freshwater fish that proclaimed as natural remedies to various illnesses by local communities without scientific evidence. Therefore, the objective of this study was to evaluate the effect of oral administration of different doses of CS extract (1000 mg/day and 500 mg/day) on the level of cartilage marker, Cartilage Oligomeric Protein (COMP) and inflammatory markers, Cyclooxgenase-2 (COX-2) and Prostaglandin E2 (PGE2) and compared within Glucosamine Sulphate (GS) treatment in KOA patients. One hundred and forty-eight patients were enrolled in this randomized, double-blind, placebo-controlled trial comparing the effect of two doses of oral CS extract (1000 mg/day and 500 mg/day) and glucosamine sulphate (GS) with the placebo group. Blood samples were collected at different-time period (baseline and six months) to assess the level of COMP, COX-2 and PGE2 using commercially available kits and the result with p<0.05 considered as statistically significant. There was a significant reduction of COX-2 level in both doses of the CS extract groups and GS group compared to the placebo group patients. Reduction of COMP level in both doses of CS extract groups might suggest the chondroprotective effect of CS extract on KOA patients. However, there was no significant difference found in the PGE2 level. Comparison between CS 1000mg/day and CS 500 mg/day groups with GS group showed a significant reduction in COX-2 level. In conclusion, orally administrated CS extract can serve as potential candidate in the treatment of KOA patients. However, further studies required to understand the mechanism of CS action.